BIODIVERSITE ET COMPLEXE D’ESPECES Perinereis cultrifera: UN EXEMPLE DE SPECIATION (Sciences & Technologie. C, Biotechnologies, 2007)
The  tools  of  measured  intra-specific  biodiversity  are  generaly  based  for  the  phenotypics' characters or the visible characters of the populations. However, genetic measures turn out to be usually very useful when we are try to distinguish among populations. A comparative study between the two epitokous forms of Perenereis cultrifera located in English Channel and the Mediterranean Sea, showed significant morphological and biochemical differences allowing the distinction of the two forms. The work is the first time that two-dimensional electrophoresis analysis of proteins has been applied to polychaetes in order to analyse levels and patterns of genetic differentiation between populations. Congruence of all reported  results from ecological, morphological and  biochemical investigations agree with the assignment that P. cultrifera is complex of species.